UTILIZING ONLINE MEDIA TO RAISE PUBLIC AWARENESS ABOUT PUBLIC HEALTH - Siswanta Siswanta (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2018)
The purpose of this research is to analyze the digital media as a primary health information source websites and its effects on individuals both tangible and intangible. Result of this research may be can help to explain the phenomena of the credibility of online media. Most importantly, the research tries to give contributions to the online media as message senders and individual as receivers or users. Based on a case study, this research studies the credibility of online media as a source of health information. This research has two aims, first to investigate some depth of understanding of how the internet’s users seeking health information via online. Second, to identify the framework which has been theoretically explored and empirically demonstrated to describe the process of communication activities in cyberspace with the digital media as a health information source to fullfill their information needs. Semi-structured and online interviews with relevant online digital media users as well as important informans, are truly conducted. Results?showed?that?cognitive?factors?are?more significant?used to?describe several communication activities?for seeking health information in cyber space. In this case, information about the health care problem by nettizen perceived as a form of a very urgent needs for the nettizen having health problems. Credibility is the criteria into consideration for nettizen to access online media in order to meet the needs of health information quickly and accurately. Online media that explicitly affiliated with professional organizations such as Ikatan Dokter Indonesia (IDI) by nettizen are perceived as a source of health information that has a high level of credibility